(untitled) (Eurasian Research Bulletin, 2025)
In the article, on the example of Uzbek prose, the role of false expectations in the breakdown of the plot is analyzed from a linguopoetic and pragmatic point of view. The manifestation of the unexpected phenomenon in the literary text, as well as the linguopoetic and philosophical foundations of the phenomenon are analyzed, and its importance as an aesthetic tool that activates the reader’s perception is justified.